PENERAPAN PENDEKATAN KONSTRUKTIVISME UNTUK MENINGKATKAN PEMBELAJARAN STRATEGI BELAJAR MENGAJAR - Budi Utami; Sugiharto Sugiharto; Nurma Yunita Indriyanti (PAEDAGOGIA, 2010)
The aims of this study is to examine the effectiveness of learning with aconstructivist approach that is applied on Teaching and Learning Strategies course inimproving the quality of the learning process and student achievement of competencystandards and to identify the perceptions of students regarding the application ofconstructivist approaches to learning Teaching and Learning Strategies course atChemical Education Department, Teacher Training And Education Faculty, SebelasMaret University. This study uses Classroom Action Research (CAR) procedure, whichconsists of two cycles. Each cycle changes are made in accordance with the desiredpurpose of the study. To describe the action research was used procedures includeplanning (planning), action (action), observation (observation) and reflection (reflection).The subjects of this study are students participating in Teaching and LearningStrategies course at Chemical Education Department, Teacher Training And EducationFaculty, Sebelas Maret University. Instruments and data collection techniques used werequestionnaire, observation sheets, home work and giving tests. Observations are used toobserve students' activity during the learning process. Testing and delivery of tasks usedto reveal the mastery of the material and learning outcomes of students in the attainmentof a predetermined standard of competence. Data analysis using descriptive analysiswith the percentages. The results showed that the application of constructivistapproaches to learning Teaching and Learning Strategies course has proven to increaselearning effectiveness both in terms of both process and learning outcomes. Resultsquestionnaire collected about students' perception was that it could be concluded that theapplication of constructivist approach has made the learning process of teaching andlearning strategies to be interesting, more fun and not boring, the students are moreenthusiastic about learning, encouraging students to learn independently and completetasks as well as possible, more students understanding the material and master thecompetencies in teaching and learning strategies.